Tradisi Pengobatan Sapulei Pada Masyarakat Desa Gunung Sejuk - Ayyuh S Ayyuh S; La Ode Dirman; Rahmat Sewa Suraya (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
The sapulei tradition is a tradition originating from the village of Gunung Sejuk wich is used to treat a skin disease called humendeno. The purpose of this study was to describe the form of traditional sapulei medicane. To analyze the function of the sapulei tradition. The method used in the research is descriptive method using a qualitative approach. Data collection techniques are carried out through interviews, observation, and documentation. The technique of determining informants in this study was carried out by purpose sampling. Activities in data analysis are collecting data, presenting data and drawing conclusions. The results of this study indicate that the form of sapulei treatment is its implementation using several nedia such as water (e’e), coconut milk (kunde’e coconut milk), and rubbing oli (mina goso). The existence of the sapulei tradition is a function of solidarity and a function of religion ehich is a factor of survival of sapulei. The aspect of being threatned with extinction is the existence of a modern medical system that causes change in peolple’s mindets.